Pelatihan Inovasi Pengolahan Pisang Menjadi Keripik Pisang Pada Mahasiswa Kelas A - Sarty Syarbiah; Tauwi Tauwi (Lembaga Pengembangan Kinerja Dosen, 2025)
The training activity on processing bananas into cheese banana chips for 4th semester students of class A who program the Agroindustry course at the Faculty of Agriculture, Lakidende University has been running well. This activity also received a positive response from students who became participants and were able to make a good contribution. 85% of the 4th semester students of class A who took part in the training were able to make cheese banana chips and 15% of the participants were not able to make cheese banana chips. This training is expected to be a means for students to increase the economic value of bananas and can be used as a home business so that it can increase family income.